Counselling on the correct use of antibiotics to prevent antibiotic resistance and the use of family medicinal plants (toga) for health - Astuty, Meilinda Windy; Solehah, Santi; Ambarwati, Suci; Rahman, Zihni Mahira; Silpia, Rena; Ramdani, Qisti Cahya Putri; Ramdhani, Salma Fitria (Journal of Health Management and Pharmacy Exploration, 2025)
A significant increase in the use of antibiotics in the community is often not matched by a proper understanding of their use, potentially leading to antibiotic resistance. This research aims to educate the community about the importance of proper antibiotic use and the utilization of Family Medicinal Plants (TOGA) as alternative medicine. Community service activities were carried out on November 24, 2024 in Salam Mulya Village, Pondok Salam District, Purwakarta Regency, in collaboration with Holistic Purwakarta Hospital. The methods used included education and discussion, with the distribution of brochures containing information on the use of antibiotics and TOGA. The results of the activity showed that the community showed high enthusiasm for the education provided, with 50 participants attending and actively participating in the discussion. The positive response from the community showed an increased understanding of the importance of the correct use of antibiotics and the utilization of herbal medicines. It is hoped that this activity can be continued and developed to increase public awareness about health.